2003
DOI: 10.1161/01.atv.0000070546.16946.3a
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin, Caveolae, and Endothelial Cell Function

Abstract: Abstract-Caveolae are 50-to 100-nm cell-surface plasma membrane invaginations observed in terminally differentiated cells. They are particularly abundant in endothelial cells, where they are believed to play a major role in the regulation of endothelial vesicular trafficking and signal transduction. The use of caveolin-1-deficient mice has provided many new insights into the roles of caveolae and caveolin-1 in the regulation of endothelial cell function. These novel findings suggest an important role for caveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
255
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(285 citation statements)
references
References 95 publications
11
255
1
1
Order By: Relevance
“…The most common uptake mechanism in endothelial cells is the caveolae‐mediated uptake32 but it has been demonstrated that PAMAM dendrimers are taken up via a clathrin‐mediated pathway 33. To better understand the underlying uptake mechanism, we investigated the couptake of DSA with markers for both pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The most common uptake mechanism in endothelial cells is the caveolae‐mediated uptake32 but it has been demonstrated that PAMAM dendrimers are taken up via a clathrin‐mediated pathway 33. To better understand the underlying uptake mechanism, we investigated the couptake of DSA with markers for both pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Research on caveolae and caveolin-1 may be of future interest, because endothelial cells exhibit high levels of caveolin-1. Caveolin-1 has been implicated in the regulation of eNOS turnover and consequently in NO release as a result of shear stress (142).…”
Section: New Research On Endotheliummentioning
confidence: 99%
“…Endothelial cells are known to express the highest levels of caveolin-1. 76 Virgintino et al 77 have reported that caveolin-1 and -2 are found in rat microvessels, and caveolin-1 is expressed in the human BBB. In the primate BBB, confocal microscopic studies indicate caveolin-1 is found in both endothelium and astrocytes.…”
Section: Caveolin-1 In Bbb Endotheliamentioning
confidence: 99%
“…76 Caveolin, a 21-to 24-kDa protein, is a principal structural component of caveolae, and three caveolin genes (caveolin-1, -2, and -3) have been identified. Endothelial cells are known to express the highest levels of caveolin-1.…”
Section: Caveolin-1 In Bbb Endotheliamentioning
confidence: 99%
See 1 more Smart Citation